To solve for x, let's simplify the equation step by step.
Starting with the left side of the equation:
78(-32 - 48x) + 36 = 23(-33x - 18) - 10x
Using the distributive property on the left side:
-2496 - 3744x + 36 = -759x - 414 - 10x
Combining like terms on the right side:
-2496 - 3744x + 36 = -769x - 414
Simplifying:
-3744x - 2460 = -769x - 414
Now, let's isolate the x term on one side of the equation.
Adding 769x to both sides:
769x - 3744x - 2460 + 769x = -769x - 414 + 769x
Combining like terms:
538x - 2460 = -414
Adding 2460 to both sides:
538x - 2460 + 2460 = -414 + 2460
Simplifying:
538x = 2046
Dividing both sides by 538:
x = 2046/538
Simplifying the fraction:
x = 3.81
Therefore, x = 3.81.
Question
Solve for x.
78(−32−48x)+36=23(−33x−18)−10x
Enter your answer in the box.
x =
1 answer